Comparison of test performance of commercial anti-SARS-CoV-2 immunoassays in serum and plasma samples - Haselmann, Verena; Kittel, Maximilian; Gerhards, Catharina; Thiaucourt, Margot; Eichner, Romy; Costina, Victor; Neumaier, Michael (Clinica chimica acta, 2020)
Background - For epidemiologic, social and economic reasons, assessment of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection prevalence and immunity are important to adapt decisions to current demands. Hence, immunoassays for detection of anti-SARS-CoV-2 antibodies are introduced rapidly without requiring FDA emergency use authorization approval. Thus, evaluation of test performance predominantly relies on laboratories. This study aimed to evaluate the test performance of recently launched commercial immunoassays in serum and plasma samples. - Methods - 51 serum samples from 26 patients with confirmed SARS-CoV-2 infection after end of quarantine and 25 control patients were analyzed using anti-SARS-CoV-2 IgG immunoassays from Roche, Euroimmun and Epitope to assess diagnostic sensitivity and specificity. 20 matching pairs of serum and plasma samples were included to analyze comparability between different specimens. - Results - Overall, a diagnostic sensitivity of 92.3%, 96.2-100% and 100% with a respective diagnostic specificity of 100%, 100% and 84-86% for the immunoassays from Roche, Euroimmun and Epitope were determined. In total, 84-96% of samples were correctly classified as negative and 92.3-95.2% as positive. The level of concordance between plasma- and serum-based testing diverged between the assays (Epitope r2 = 0.97; Euroimmun r2 = 0.91; Roche r2 = 0.76). - Conclusions - The immunoassays from Euroimmun and Roche revealed a higher specificity than the Epitope assay without a substantial drop of diagnostic sensitivity. Significant differences between plasma- and serum-based testing highlights the need for determination of appropriate cut-offs per specimen type. Hence, there is an urgent need for test harmonization and establishment of quality standards for an appropriate use of COVID-19 serological tests.
Gesehen am 03.02.2021